THE MODEL OF CHALLENGES OF SMART CONTRACT BASED ON BLOCKCHAIN TECHNOLOGY AND DISTRIBUTED LEDGER USING META-SYNTHESIS RESEARCH METHOD - Pooya, Amin; Jafarnejad Chaghoushi, Ahmad; Shokohyar, Sajad; karimizand, Mahdi (Gênero & Direito, 2020)
Many believe that smart contract can provide an innovative solution to some of the real-world problems. Thus, it is expected that blockchain-based smart contracts can dramatically increase economic efficiency and productivity in financial, banking and capital markets. In fact, smart contracts are a powerful novel tool for major changes in the financial, legal and contractual systems of the future, which will change the business model, create efficiency and added value, reduce legal disputes and increase the speed and transparency of financial transactions. Another innovative solution of smart contracts is their wide application in the internet of objects (IoT). For example, smart contract can be used to track goods in smart transport system, or it can be applied in future smart cars without a driver in order to pay for gasoline when fueling or pay for the insurance in the case of an accident automatically and immediately. Due to the widespread applications of smart contract in e-government, supply chain, intellectual property creation, patient electronic records, electronic voting, electronic insurance, smart transport and so on, its importance is clearly identified. Therefore, considering the emergence of smart contracts and given the scattered studies in this field, an attempt has been made to present a comprehensive and systematic model of the challenges of smart contract based on blockchain technology and the distributed ledger by the systematic review of previous studies (papers published in internationally accredited journals and theses reviewed between 2016 and 2019), using a meta-synthesis qualitative research method and Sandelowski and Barroso’s (2006) seven-step model.